Paciente femenino de 10 años con discinesia ciliar primaria. - Cantillo Alvarado, Aura Madelaine (2021)
Primary ciliary dyskinesia is a rare disease of genetic origin that corresponds to the genus of primary ciliary dyskinesias. This genetically heterogeneous alteration that affects the motile cilia, since the normal hair cell is composed of approximately 250 proteins organized around an axoneme or set of longitudinal microtubules that extend from the cytoplasm to the end of the cilium. The clinical manifestations that can be detected in the neonatal period are rhinorrhea from the first days of life, neonatal distress or pneumonia with no apparent cause. During childhood, symptoms of chronic cough, asthma with poor response to treatment, the finding of bronchiectasis of unclear cause, chronic rhinosinusitis despite receiving multiple treatments, and prolonged suppurative otitis media are frequent. This clinical case is based on making known an adequate treatment for the patient, in addition to analyzing the diagnostic tests for a correct treatment and taking into account the possible respiratory infections that patients with said disease may suffer, identifying the risk factors that affect it. said pathology.